Investigating the Meaningful Learning in Chemical Separation Practicums: A Quantitative Approach - Amat, Amat; Erlina, Erlina; Ira Lestari, Ira Lestari; Masriani, Masriani; Maria Ulfah, Maria Ulfah (Universitas Pendidikan Mandalika, 2024)
Meaningful learning has an important element that is finding advantages in obtaining various information comprehensively, thereby ultimately improving learner’s abilities. This aspect can provide information to understand and enhance meaningful learning. The purpose of this research is to analyze meaningful learning in the chemical separation practicum for the Chemistry Education students at FKIP UNTAN. The type of research used is quantitative descriptive with a survey method. Data collection tools in this analysis are questionnaires and interview guidelines. The questionnaires and interviews were administered after the practicum was completed. The number of students for the questionnaire was 59 people consisting of 26 people who were interviewed, including course instructors, laboratory heads, laboratory assistants, and student representatives from classes A1, A2, A3. The research results, in terms of the affective aspect, were 64% in the good category. In terms of the cognitive aspect, a percentage of 73% was achieved in the good category, while the affective-cognitive aspect had a percentage of 66% in the good category. Based on the data obtained, it can be concluded that learning in this chemical separation practicum is meaningful.